Coated metal plate

By forming a photocatalyst layer on the metal plate containing zinc metal layer, the dissolution conditions of zinc are optimized, and the problems of insufficient improvement of antiviral function and insufficient durability in the prior art are solved, and the antiviral performance improvement of efficient and economical coating metal plates is achieved.

CN119654236APending Publication Date: 2025-03-18NIPPON STEEL CORPORATION
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202380057939.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-08
Filing Date
2023-08-08
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the prior art, there is room for improvement in the use of photocatalysts to improve the antiviral function, and the durability of the coating agent is insufficient, resulting in high operating costs.

Method used

By forming a photocatalyst layer on a metal plate with a zinc-containing metal layer, the dissolution conditions of zinc are optimized to improve the antiviral function of the coated metal plate.

Benefits of technology

A simpler manufacturing process is achieved, and the antiviral function and durability of coated metal plates are improved, reducing operating costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119654236A_ABST
    Figure CN119654236A_ABST
Patent Text Reader

Abstract

Provided is a coated metal plate which can be manufactured more easily, can further improve an antiviral function, and has durability. The present invention relates to a coated metal plate having a metal plate and a coating layer on at least one surface of the metal plate, the metal plate having a zinc-containing metal layer containing at least zinc on at least one surface, the coated metal plate having a first coating layer as the coating layer, the first coating layer is located on the outermost surface of the coated metal plate and contains at least a compound having photocatalytic activity, the average thickness of the first coating layer is 0.05-5.00 [mu] m, the total thickness from the surface of the zinc-containing metal layer to the outermost surface of the first coating layer is 15.00 [mu] m or less, and when an antiviral test specified in JIS R1756: 2020 is performed for 4 hours, the average thickness of the first coating layer is 0.05-5.00 [mu] m, and the total thickness of the first coating layer from the surface of the zinc-containing metal layer to the outermost surface of the first coating layer is 15.00 [mu] m or less. And the concentration of zinc ions eluted into the virus-containing solution is 0.60-5.00 mass%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to coated metal sheets. Background Art

[0002] In recent years, due to the impact of the new coronavirus (COVID-19), the demand for various items to have antiviral properties is increasing, and the business of applying antiviral agents to the surface of various items is booming. The application of antiviral agents can be applied to existing buildings. However, the application of antiviral agents requires high labor costs, and since the durability of the agents is insufficient, regular construction is required, and there is a problem of high operating costs.

[0003] On the other hand, there is a known technique for pre-imparting antiviral function to steel materials, for example, as in the following Patent Document 1. This technique is based on coating steel materials, and a protective layer and a photocatalyst layer are sequentially formed on the upper layer of the coated steel materials.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2009-131960 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] However, as a result of the research conducted by the present inventors, it has been found that the technology using a photocatalyst as disclosed in Patent Document 1 described above has room for further improvement in terms of enhancing the antiviral function.

[0009] Based on this finding, an object of the present invention is to provide a coated metal plate that can be manufactured more simply, has a further improved antiviral function, and has durability.

[0010] Solutions for solving problems

[0011] In order to solve the above problems, the present inventors conducted in-depth research and experimentally found the following insights: if a member formed by further forming a photocatalyst layer on a metal plate having a metal layer containing zinc is subjected to the antiviral test specified in JISR1756:2020, the metal plate in which zinc is easily dissolved into a virus-containing liquid has better antiviral properties. Based on this insight, the present inventors conducted further research and found the following insights, which led to the completion of the present invention: by achieving conditions in which zinc is easily dissolved, the antiviral function of the coated metal plate can be further improved.

[0012] The gist of the present invention completed based on this finding is as follows.

[0013] (1) A coated metal plate comprising a metal plate and a coating layer located on at least one surface of the metal plate, wherein the metal plate is a metal plate having a zinc-containing metal layer containing at least zinc on at least one surface, the coated metal plate having a first coating layer as the coating layer, the first coating layer being located on the outermost surface of the coated metal plate and containing at least a compound having photocatalytic activity, the first coating layer having an average thickness of 0.05 to 5.00 μm, a total thickness from the surface of the zinc-containing metal layer to the outermost surface of the first coating layer being not more than 15.0 μm, and a concentration of zinc ions eluted into a virus-containing liquid in a 4-hour antiviral test specified in JIS R1756:2020 being 0.60 to 5.00 mass %.

[0014] (2) The coated metal sheet according to (1), wherein the thickness of the first coating layer is 0.05 to 0.95 μm, and the total thickness from the surface of the zinc-containing metal layer to the outermost surface of the first coating layer is less than 1.0 μm.

[0015] (3) The coated metal sheet according to (1) or (2), wherein the total content of elements having a higher potential than zinc in the coating layer is 0 to 20.0% by mass.

[0016] (4) The coated metal sheet according to (1), wherein the first coating layer further contains at least one element selected from the group consisting of Zn, Cu, Fe, Ni, and Ag.

[0017] (5) The coated metal sheet according to (1), wherein the first coating layer further contains at least one element of Si and Zr, and the total content of the elements is 5 to 50% by mass in terms of silicon dioxide for Si and zirconium oxide for Zr.

[0018] (6) A coated metal plate comprising a metal plate and a coating layer located on at least one surface of the metal plate, wherein the coated metal plate has a first coating layer as the coating layer, the first coating layer being located on the outermost surface of the coated metal plate and containing a compound having photocatalytic activity and 0.2 to 20.0 mass % of zinc element calculated as metallic Zn, the first coating layer having an average thickness of 0.05 to 5.00 μm, and a total thickness from the surface of the metal plate to the outermost surface of the first coating layer being less than 60.0 μm, and when subjected to a 4-hour antiviral test specified in JIS R1756:2020, the concentration of zinc ions eluted into a virus-containing liquid is 0.60 to 5.00 mass %.

[0019] (7) The coated metal sheet according to (6), wherein the total content of elements having a higher potential than zinc in the coating layer is 0 to 20.0% by mass.

[0020] (8) The coated metal sheet according to (6) or (7), wherein the first coating layer further contains at least one element selected from the group consisting of Cu, Fe, Ni, and Ag.

[0021] (9) The coated metal sheet according to (6), wherein the first coating layer further contains at least one element of Si and Zr, and the total content of the elements is 5 to 50% by mass in terms of silicon dioxide for Si and zirconium oxide for Zr.

[0022] (10) A coated metal plate according to (1) or (6), wherein the coated metal plate further comprises a second coating layer as the coating layer, wherein the second coating layer is located below the first coating layer and is formed of an inorganic component, wherein the second coating layer contains at least one element of Si and Zr as the inorganic component, and wherein the average thickness of the second coating layer is 0.05 to 5.00 μm.

[0023] (11) The coated metal sheet according to (10), wherein the second coating layer further contains at least one element of P and V as the inorganic component.

[0024] (12) The coated metal sheet according to (10), wherein the second coating layer further contains at least one element selected from the group consisting of Zn, Cu, Fe, Ni, and Ag.

[0025] (13) The coated metal plate according to (10), wherein the coated metal plate further comprises a third coating layer as the coating layer, the third coating layer is located below the second coating layer, contains a resin component, and has an average thickness of 0.50 to 14.00 μm.

[0026] (14) The coated metal sheet according to (13), wherein the third coating layer further contains a colorant.

[0027] (15) The coated metal sheet according to (1) or (6), wherein the compound having photocatalytic activity is anatase-type titanium oxide.

[0028] (16) The coated metal sheet according to (15), wherein the compound having photocatalytic activity is a metal-supported titanium oxide in which at least one metal of Cu and Fe is supported on titanium oxide.

[0029] (17) The coated metal sheet according to (1), wherein the metal sheet is a zinc-based plated steel sheet having a zinc-based plated layer as the zinc-containing metal layer.

[0030] (18) The coated metal sheet according to (17), wherein the zinc-based plating layer is a plating layer containing 30 mass % or more of Zn in terms of metallic Zn.

[0031] (19) The coated metal sheet according to (17), wherein the zinc-based plating layer is any one of a zinc plating layer, a zinc-aluminum alloy plating layer, a zinc-aluminum-magnesium alloy plating layer, a zinc-nickel alloy plating layer, and a zinc-iron alloy plating layer.

[0032] (20) The coated metal plate according to (1) or (6), wherein there are wires on the surface of the metal plate along the rolling direction of the metal plate.

[0033] (21) The coated metal sheet according to (1), wherein a zinc flower pattern exists on the surface of the zinc-containing metal layer.

[0034] Effects of the Invention

[0035] As described above, according to the present invention, it is possible to provide a coated metal plate that can be manufactured more simply, has durability, and has a further improved antiviral function. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is an explanatory diagram schematically showing an example of the structure of the coated metal plate according to the first embodiment of the present invention.

[0037] Figure 2A This is an explanatory diagram schematically showing another example of the structure of the coated metal plate according to the first embodiment of the present invention.

[0038] Figure 2B This is an explanatory diagram schematically showing another example of the structure of the coated metal plate according to the first embodiment of the present invention.

[0039] Figure 3A This is an explanatory diagram schematically showing another example of the structure of the coated metal plate according to the first embodiment of the present invention.

[0040] Figure 3B This is an explanatory diagram schematically showing another example of the structure of the coated metal plate according to the first embodiment of the present invention.

[0041] Figure 4 This is an explanatory diagram schematically showing an example of the structure of a coated metal plate according to the second embodiment of the present invention.

[0042] Figure 5AThis is an explanatory diagram schematically showing another example of the structure of the coated metal plate according to the second embodiment of the present invention.

[0043] Figure 5B This is an explanatory diagram schematically showing another example of the structure of the coated metal plate according to the second embodiment of the present invention.

[0044] Fig. 6A This is an explanatory diagram schematically showing another example of the structure of the coated metal plate according to the second embodiment of the present invention.

[0045] Figure 6B This is an explanatory diagram schematically showing another example of the structure of the coated metal plate according to the second embodiment of the present invention. DETAILED DESCRIPTION

[0046] The preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings. In addition, in this specification and the drawings, components having substantially the same functional configuration are denoted by the same reference numerals to omit repeated description.

[0047] 《First Implementation Method》

[0048] Hereinafter, first, a coated metal plate according to a first embodiment of the present invention will be described in detail.

[0049] A first aspect of the present invention relates to a coated metal plate having a metal plate and a coating layer located on at least one surface of the metal plate, wherein the metal plate has a zinc-containing metal layer containing at least zinc on at least one surface of the metal plate.

[0050] (For painted metal sheets)

[0051] <Structure of painted metal sheet>

[0052] Below, first, while referring to Figure 1 , while describing the structure of the coated metal plate according to the first embodiment of the present invention. Figure 1 This is an explanatory diagram schematically showing an example of the structure of the coated metal plate according to the present embodiment.

[0053] like Figure 1 As schematically shown, the coated metal plate 1 according to the first embodiment of the present invention has a coating layer on at least one surface of the metal plate, and includes at least a metal plate 10 and a photocatalyst layer 20 as an example of a first coating layer as the coating layer.

[0054] [For metal plate 10]

[0055] In the coated metal plate 1 of the present embodiment, the metal plate 10 includes a base metal 11 as a base material of the metal plate 10 and a zinc-containing metal layer 13 as a metal layer containing at least zinc.

[0056] Here, various metal plates can be used as the base metal 11. Examples of such metal plates include various steel plates, aluminum plates, and stainless steel plates, and the metal plates can be selected according to the strength and characteristics required of the base metal 11.

[0057] In addition, the zinc-containing metal layer 13 is a metal layer provided on the surface of the base metal 11, and contains at least zinc. The presence of such a zinc-containing metal layer 13 on the surface of the base metal 11 causes the dissolution of zinc into the virus-containing liquid in the antiviral test specified in JIS R1756:2020, as discovered by the inventors. As a result, the antiviral function of the coated metal plate 1 can be further improved over a longer period of time by a simpler method.

[0058] In more detail, the zinc-containing metal layer 13 preferably contains more than 30% by mass of zinc in terms of metal Zn. In addition, the zinc-containing metal layer 13 may also contain impurities. By making the zinc content in the zinc-containing metal layer 13 more than 30% by mass, it is possible to further increase the amount of zinc dissolved into the above-mentioned virus-containing liquid while ensuring the corrosion resistance of the parent metal 11. Thereby, the antiviral function of the coated metal plate 1 can be further improved. The zinc content in the zinc-containing metal layer 13 is more preferably more than 40% by mass, and more preferably more than 70% by mass. In addition, the higher the zinc content in the zinc-containing metal layer 13, the better, and the zinc content in the zinc-containing metal layer 13 may also be 100% by mass.

[0059] As such a zinc-containing metal layer 13, for example, a zinc vapor-deposited layer formed by vapor-depositing metal zinc, or a zinc-based plating layer as a plating layer containing zinc can be cited. Here, from the viewpoint of easily manufacturing the zinc-based plating layer at excellent manufacturing cost by using various zinc-based plating production lines that have already been set up, it is preferred to provide a zinc-based plating layer as the zinc-containing metal layer 13.

[0060] The zinc coating preferably used as the zinc-containing metal layer 13 is a zinc coating containing more than 30% by mass of zinc in terms of metal Zn conversion. In addition, the zinc coating may also contain impurities. By making the zinc content in the zinc coating more than 30% by mass, the amount of zinc dissolved in the virus-containing liquid can be further increased while ensuring the corrosion resistance of the base metal 11, and the antiviral function of the coated metal plate 1 can be further improved. The zinc content in the zinc coating is more preferably more than 40% by mass, and more preferably more than 70% by mass. In addition, the zinc content in the zinc coating may also be 100% by mass.

[0061] As such zinc-based plating, for example, various platings such as zinc plating, zinc-aluminum alloy plating, zinc-aluminum-magnesium alloy plating, zinc-nickel alloy plating, zinc-iron alloy plating, etc. can be cited. In addition, from the viewpoint of further increasing the amount of zinc elution, it is more preferable to provide a zinc-nickel alloy plating or a zinc-iron alloy plating as the zinc-based plating.

[0062] In particular, element Fe is an element that promotes the dissolution of zinc from the viewpoint of ionization tendency. The coexistence of metal Fe and zinc is advantageous in terms of potential from the viewpoint of the dissolution of zinc, and is therefore preferred.

[0063] The amount of the zinc-containing metal layer 13 deposited on each side of the base metal 11 is preferably 8 g / m2 in terms of metal Zn. 2 More preferably 17 g / m 2 By setting the adhesion amount to 8 g / m 2 More preferably, 17 g / m 2 In this way, a sufficient amount of zinc can be dissolved while ensuring the corrosion resistance of the base metal 11. On the other hand, the amount of the zinc-containing metal layer 13 is preferably 250 g / m2 in terms of metal Zn per single surface of the base metal 11. 2 Below, more preferably 170g / m 2 By setting the adhesion amount to 250g / m 2 Below, more preferably set to 170g / m 2 In this way, a sufficient amount of zinc can be eluted while ensuring the corrosion resistance of the base metal 11 .

[0064] As described above, it is more convenient to use various zinc-based plated steel sheets having various zinc-based plating layers as described above as the metal sheet 10 having the zinc-containing metal layer 13 .

[0065] Here, the thickness of the metal plate 10 as described above is not particularly limited, and may be appropriately set according to mechanical strength (for example, tensile strength, etc.), workability, etc. required for the coated metal plate 1 of the present embodiment.

[0066] In addition, the surface of the zinc-containing metal layer 13 may have various patterns such as a wire drawing pattern and a zinc flower pattern along the rolling direction of the base metal 11. By providing such patterns, the design of the coated metal plate 1 can be further improved.

[0067] In addition, the wire drawing pattern is a pattern realized by forming fine concavoconvexities on the surface of the zinc-containing metal layer 13, thereby increasing the surface area of ​​the zinc-containing metal layer 13. As a result, the amount of zinc eluted from the zinc-containing metal layer 13 can be further increased, which is more preferable not only from the viewpoint of appearance design but also from the viewpoint of antiviral property.

[0068] In addition, Figure 1 In the figure, the zinc-containing metal layer 13 is formed on one surface of the base metal 11 , but the zinc-containing metal layer 13 may be formed on both surfaces of the base metal 11 .

[0069] [Regarding the photocatalyst layer 20]

[0070] In the coated metal plate 1 of this embodiment, as Figure 1 As schematically shown, the photocatalyst layer 20 as an example of the first coating layer is a layer located on the outermost surface of the coating layer on at least one surface of the metal plate 10, and contains at least a compound having photocatalytic activity (hereinafter sometimes referred to as "photocatalyst compound"). The photocatalyst layer 20 contains a compound having photocatalytic activity, so that the compound having photocatalytic activity produces a photocatalytic reaction due to light (especially light in the ultraviolet to visible light band) incident on the photocatalyst layer 20. As a result, in the photocatalyst layer 20 of the present embodiment, various photocatalytic effects such as antiviral effect and bactericidal effect are exhibited. Therefore, the coated metal plate 1 of the present embodiment can achieve various characteristics such as antiviral effect and bactericidal effect.

[0071] For such compounds having photocatalytic activity, there are: compounds that mainly react with light in the ultraviolet light band (more specifically, are excited by light in the ultraviolet light band) and exhibit photocatalytic activity; and compounds that mainly react with light in the visible light band (more specifically, are excited by light in the visible light band) and exhibit photocatalytic activity.

[0072] Examples of compounds that react with light in the ultraviolet band and exhibit photocatalytic activity include metal oxides such as titanium oxide (more specifically, anatase-type titanium oxide), zinc oxide, cerium oxide, tin oxide, bismuth oxide, zirconium oxide, tungsten oxide, chromium oxide, molybdenum oxide, iron oxide, nickel oxide, ruthenium oxide, cobalt oxide, copper oxide, manganese oxide, germanium oxide, lead oxide, cadmium oxide, vanadium oxide, niobium oxide, tantalum oxide, rhodium oxide, and rhenium oxide; metal sulfides such as cadmium sulfide and zinc sulfide; and titanium compounds such as strontium titanate and barium titanate. Among them, as compounds that react with light in the ultraviolet band and exhibit photocatalytic activity, anatase-type titanium oxide, zinc oxide, tin oxide, zirconium oxide, tungsten oxide, iron oxide, niobium oxide, and strontium titanate are particularly preferably used, and anatase-type titanium oxide is further preferably used.

[0073] In addition, as compounds that react with light in the visible light band and exhibit photocatalytic activity, for example, metal-loaded titanium oxide (more specifically, anatase-type titanium oxide) in which titanium oxide is loaded with at least one metal of Cu and Fe, anatase-type titanium oxide in which anatase-type titanium oxide is loaded with Cr, V, Mn, Ni, and Pt, anatase-type titanium oxide in which anatase-type titanium oxide is doped with anions such as nitrogen and sulfur, and a solid solution of AgNbO3 and SrTiO3, etc. Among them, anatase-type titanium oxide in which anatase-type titanium oxide is loaded with at least one metal of Cu and Fe is more preferably used.

[0074] In particular, the adhered Cu exhibits the effect of promoting the dissolution of zinc from the zinc-containing metal layer 13 as described above, and therefore, it is particularly preferable to use anatase-type titanium oxide supporting Cu.

[0075] In the photocatalyst compound, the average particle size (primary particle size) of anatase titanium oxide (including those in a state where a metal is loaded) is preferably greater than 5 nm. By making the average particle size (primary particle size) of anatase titanium oxide greater than 5 nm, anatase titanium oxide can be more evenly dispersed in the photocatalyst layer 20. The average particle size (primary particle size) of anatase titanium oxide is more preferably greater than 20 nm. In addition, the average particle size (primary particle size) of anatase titanium oxide (including those in a state where a metal is loaded) is preferably less than 200 nm. By making the average particle size (primary particle size) of anatase titanium oxide less than 200 nm, anatase titanium oxide can be more evenly dispersed in the photocatalyst layer 20 while suppressing excessive aggregation of anatase titanium oxide in the photocatalyst layer 20. The average particle size (primary particle size) of anatase titanium oxide is more preferably less than 100 nm.

[0076] Here, the average particle size of the above-mentioned anatase titanium oxide can be measured, for example, by a dynamic light scattering method using a laser. This method can easily obtain a measured value with high accuracy. Wherein, when the particles of anatase titanium oxide aggregate to a certain extent, since it is possible to measure the size of the aggregate (aggregate particle size), it is preferably combined with a transmission electron microscope (TEM) to directly confirm the primary particle size. The result of TEM observation is that, when the presence of aggregated particles is confirmed, it is preferably to change the dispersion conditions and measure again by a dynamic light scattering method. In addition, in the case of being difficult to be completely dispersed to the level of primary particles, the size of the primary particles observed / measured with TEM can also be used as the primary particle size. In this case, the experience of the inventors shows that by taking arbitrarily selected particles of about 100 or more as the measurement object, a value representing the overall size of the particles can be obtained.

[0077] In addition, for the coated metal plate 1 on which the photocatalyst layer 20 has been formed, when the average particle size of the anatase-type titanium oxide contained in the photocatalyst layer 20 is measured afterwards, it can be done as follows. That is, a transmission electron microscope (TEM) can be used to observe or analyze the cross-section of the photocatalyst layer 20 when it is cut in the thickness direction. By using TEM, the primary particle size of the photocatalyst compound can be measured. In addition, by performing EDS analysis together with TEM, the elements contained in the photocatalyst compound can be measured. Furthermore, by electron beam diffraction, the crystal structure of the photocatalyst compound (for example, whether it is anatase-type or rutile-type in the case of titanium oxide) can be known. The experience of the inventors shows that by taking arbitrarily selected approximately 100 or more particles as the measurement object, a value representing the overall particle can be obtained.

[0078] Here, the concentration of anatase titanium oxide (including those in a state where metal is loaded) in the photocatalyst layer 20 is preferably 50% by mass or more in terms of titanium oxide conversion. By making the concentration of anatase titanium oxide in the photocatalyst layer 20 to be 50% by mass or more, various photocatalytic effects, such as antiviral effects, can be reliably exhibited. The concentration of anatase titanium oxide in the photocatalyst layer 20 is more preferably 60% by mass or more in terms of titanium oxide conversion. In addition, the concentration of anatase titanium oxide (including those in a state where metal is loaded) in the photocatalyst layer 20 is preferably 95% by mass or less in terms of titanium oxide conversion. By making the concentration of anatase titanium oxide in the photocatalyst layer 20 to be 95% by mass or less, various photocatalytic effects, such as antiviral effects, can be exhibited while suppressing the increase in manufacturing costs. The concentration of anatase titanium oxide in the photocatalyst layer 20 is more preferably 80% by mass or less in terms of titanium oxide conversion.

[0079] In addition, similarly to the above, photocatalytic compounds other than anatase-type titanium oxide preferably have an average particle size of 5 to 200 nm, and the concentration thereof is preferably 50 to 95% by mass.

[0080] As the photocatalyst compound represented by the anatase-type titanium oxide mentioned above, a granular substance may be used as a matter of course, and a sol-like substance that cannot be called a granular substance or a substance generated by heating a metal complex may also be used as needed.

[0081] In addition, the photocatalyst layer 20 preferably also contains at least one element of Si and Zr, and the total concentration of the element is 5% by mass or more when converted to silicon dioxide for Si and to zirconium oxide for Zr. In other words, the photocatalyst layer 20 is preferably an inorganic coating having a skeleton of an inorganic component having a three-dimensional network structure containing at least one element of Si and Zr and having impurities as the case may be, and the total concentration of at least one element of Si and Zr is 5% by mass or more when converted to silicon dioxide for Si and to zirconium oxide for Zr. By containing at least one element of Si and Zr at the above-mentioned concentration, a photocatalyst layer 20 with better corrosion resistance can be achieved. The total content of at least one element of Si and Zr is more preferably 10% by mass or more. Here, the inorganic component refers to a component that does not contain an organic resin.

[0082] In addition, it is preferred that the photocatalyst layer 20 also contains at least one element of Si and Zr, and the total concentration of the element is 50% by mass or less when converted to silicon dioxide for Si and zirconium oxide for Zr. By containing at least one element of Si and Zr at the above concentration, a photocatalyst layer 20 with better corrosion resistance can be achieved. The total content of at least one element of Si and Zr is more preferably 40% by mass or less. Here, the contained Si or Zr is preferably excellent in light transmittance, and is preferably an inorganic component that is not easily affected by decomposition caused by a photocatalyst. As such inorganic components containing Si and Zr, for example, silicon dioxide and zirconium oxide can be listed.

[0083] In addition, in addition to containing the above-mentioned photocatalyst compound, at least one element of Si and Zr, the photocatalyst layer 20 preferably also contains at least one element selected from the group consisting of Zn, Cu, Fe, Ni, and Ag. Here, the elements Cu, Fe, Ni, and Ag are elements that promote the dissolution of zinc from the above-mentioned zinc-containing metal layer 13, so by making the photocatalyst layer 20 also contain these elements, more zinc is dissolved from the zinc-containing metal layer 13, so it is preferred. Moreover, the elements Cu, Zn, and Ag are also elements that show antibacterial effects, so they are particularly preferred. In addition, by making the photocatalyst layer 20 also contain the element Zn, it is possible to seek a further increase in the amount of zinc dissolved from the coated metal plate 1, so it is more preferred.

[0084] The total content of at least one element selected from the group consisting of Zn, Cu, Fe, Ni, and Ag in the photocatalyst layer 20 is preferably 0.2% by mass or more in terms of metal element conversion. By making the total content of the above-mentioned metal elements 0.2% by mass or more, the above-mentioned effect can be presented in a more preferred state. The total content of the above-mentioned metal elements is more preferably 0.6% by mass or more, and further preferably 1.0% by mass or more. On the other hand, the total content of at least one element selected from the group consisting of Zn, Cu, Fe, Ni, and Ag in the photocatalyst layer 20 is preferably 5.0% by mass or less in terms of metal element conversion. By making the total content of the above-mentioned metal elements 5.0% by mass or less, the above-mentioned effect can be presented in an unsaturated manner while ensuring the content of the photocatalyst compound. The total content of the above-mentioned metal elements is more preferably 3.5% by mass or less, and further preferably 2.5% by mass or less.

[0085] Furthermore, the photocatalyst layer 20 containing the above-mentioned photocatalyst compound may contain an adsorbent such as an antimicrobial agent, activated carbon, or zeolite as necessary within a range not impairing the effects of the present invention.

[0086] The average thickness d1 of the photocatalyst layer 20 (in Figure 1 In the case of the layer structure shown in FIG. 1 , the total thickness d from the surface of the metal plate 10 to the outermost surface of the photocatalyst layer 20 (which can also be regarded as the outermost surface of the coating layer) is T . ) is 0.05 μm or more. When the average thickness d1 of the photocatalyst layer 20 is less than 0.05 μm, it is difficult to form a uniform film of the photocatalyst layer 20 as described above, and the obtained photocatalytic effect will be uneven, which is not preferred. By setting the average thickness d1 to be greater than 0.05 μm, the dissolution path of zinc from the zinc-containing metal layer 13 can be ensured so that zinc is fully dissolved, and the desired photocatalytic effect can be uniformly presented throughout the photocatalyst layer 20.

[0087] On the other hand, the average thickness d1 of the photocatalyst layer 20 (in Figure 1 In the case of the layer structure shown in FIG. 1 , the total thickness d from the surface of the metal plate 10 to the outermost surface of the photocatalyst layer 20 is also T. ) is less than 5.00μm. When the average thickness d1 of the photocatalyst layer 20 is greater than 5.00μm, the obtained photocatalytic effect is saturated, and on the other hand, the manufacturing cost increases, so it is not preferred. In addition, it is difficult to fully ensure the dissolution amount of zinc from the zinc-containing metal layer 13, so from this point of view, it is not preferred. In addition, since the photocatalyst layer is an inorganic coating, the processability is reduced. By setting the average thickness d1 to less than 5.00μm, it is possible to suppress the reduction in manufacturing simplicity and processability, and ensure the dissolution path of zinc from the zinc-containing metal layer 13 so that zinc is fully dissolved, and the desired photocatalytic effect is uniformly presented throughout the photocatalyst layer 20.

[0088] Usually, light passes through the photocatalyst layer 20 without hitting the photocatalyst compound with a certain degree of probability. In the past, such light that does not react with the photocatalyst compound has been unable to obtain a photocatalytic effect. In the present embodiment, by reflecting such light on the surface of the metal plate 10, the probability of light incident on the photocatalyst layer 20 colliding with the photocatalyst compound can be increased. Therefore, in the present embodiment, the photocatalytic effect can be further improved. Figure 1 In the case of the layer structure shown in FIG. 1 , the total thickness d from the surface of the metal plate 10 to the outermost surface of the photocatalyst layer 20 is T Of course, it is 5.00 μm or less. As a result, the incident light reflected from the surface of the metal plate 10 (in other words, the interface between the metal plate 10 and the photocatalyst layer 20) can be used for the photocatalytic reaction caused by the photocatalyst compound, thereby further improving the photocatalytic effect.

[0089] The average thickness d1 of the photocatalyst layer 20 is preferably 0.10 μm or more, more preferably 0.15 μm or more. In addition, the average thickness d1 of the photocatalyst layer 20 is preferably 2.00 μm or less, more preferably 1.00 μm or less, further preferably less than 1.0 μm, more preferably 0.80 μm or less, 0.60 μm or less, or 0.50 μm or less.

[0090] In addition, Figure 1 In FIG. 1 , an embodiment in which the photocatalyst layer 20 is formed on one surface of the metal plate 10 is illustrated, but the photocatalyst layer 20 may be formed on both surfaces of the metal plate 10 .

[0091] <Concentration of zinc ions eluted into virus-containing fluid in antiviral test>

[0092] The structure of the coated metal plate 1 described above is one of the conditions for making the concentration of zinc ions eluted into the virus-containing liquid within the range of 0.60 to 5.00 mass % when the antiviral test specified in JIS R1756:2020 is performed for 4 hours.

[0093] The reason why the above-mentioned structure is one of the conditions is that in the coated metal plate 1 of the present embodiment, the zinc-containing metal layer 13 is provided in an appropriate state, and the total thickness d from the surface of the metal plate 10 to the outermost surface of the photocatalyst layer 20 is 2.37mm / s. T In a specific range, an appropriate amount of zinc can be eluted from the zinc-containing metal layer 13. Thus, in the coated metal plate 1 of this embodiment, the zinc-containing metal layer 13, which is originally provided to ensure the corrosion resistance of the metal plate 10, also functions to improve the antiviral property of the coated metal plate 1.

[0094] In addition, by adjusting the adhesion amount of the zinc-containing metal layer 13, the total thickness d T , the amount of zinc eluted from the zinc-containing metal layer 13 can be controlled to a desired state. In addition, by further controlling the density of the coating layer existing on the path from the zinc-containing metal layer 13 to the outermost surface of the photocatalyst layer 20, the amount of zinc eluted from the zinc-containing metal layer 13 can also be controlled.

[0095] Here, when the zinc ion concentration in the virus-containing liquid is less than 0.60 mass %, it means that the amount of zinc eluted from the zinc-containing metal layer 13 is insufficient, and the antiviral function exhibited by the coated metal plate 1 cannot be further improved. The zinc ion concentration in the virus-containing liquid is preferably 0.90 mass % or more, and more preferably 1.20 mass % or more.

[0096] On the other hand, when the zinc ion concentration in the virus-containing liquid exceeds 5.00 mass %, the amount of zinc eluted from the zinc-containing metal layer 13 becomes too large, and the corrosion resistance of the metal plate 10 cannot be ensured. The zinc ion concentration in the virus-containing liquid is preferably 4.50 mass % or less, and more preferably 3.50 mass % or less.

[0097] In addition, in the coated metal plate 1 of the present embodiment, the total content of the element (more specifically, ion) present in the coating layer and having a potential higher than zinc is preferably less than 20.0 mass % in terms of metal element conversion. Here, as an element with a potential higher than zinc, for example, Cu, Ag, etc. can be listed. By setting the total content of the element in the coating layer and having a potential higher than zinc to less than 20.0 mass %, the zinc ion concentration in the above-mentioned virus-containing liquid can be set to less than 5.00 mass %, and it is possible to seek to further take into account excellent antiviral properties and excellent corrosion resistance. The total content of the element in the coating layer and having a potential higher than zinc is more preferably less than 15.0 mass %, more preferably less than 11.0 mass %, and more preferably less than 7.5 mass %. In addition, the lower limit of the total content of the element in the coating layer and having a potential higher than zinc is not particularly specified, and can also be 0 mass %.

[0098] Here, the above antiviral test is carried out for 4 hours according to the method specified in JIS R1756: 2020. In addition, the concentration of zinc ions eluted into the virus-containing liquid may be measured by inductively coupled plasma (ICP) emission spectrometry.

[0099] <Variation Example-1>

[0100] have Figure 1 The coated metal plate 1 of the present embodiment having the layer structure shown may also have more coating layers that function as chemical conversion coating layers between the metal plate 10 and the photocatalyst layer 20. By providing a chemical conversion coating layer between the metal plate 10 and the photocatalyst layer 20, the adhesion between the metal plate 10 and the photocatalyst layer 20 can be further improved. Furthermore, the corrosion resistance of the coated metal plate 1 of the present embodiment can also be further improved.

[0101] Below, while referring to Figure 2A and Figure 2B , while explaining in detail more coating layers that function as a chemical conversion treatment coating layer. Figure 2A and Figure 2B This is an explanatory diagram schematically showing another example of the structure of the coated metal plate according to the present embodiment.

[0102] Figure 2A and Figure 2B The schematic diagram schematically shows the layer structure of the coated metal plate 1 in which an inorganic coating layer 30 that functions as a chemical conversion coating layer is provided as an example of a second coating layer. In this case, the coated metal plate 1 of the present embodiment has an inorganic coating layer 30 that is an example of a second coating layer between the metal plate 10 and the photocatalyst layer 20 as described above.

[0103] Since photocatalyst compounds represented by anatase titanium oxide have extremely excellent oxidizability, when a coating layer is provided at a position lower than the layer where the photocatalyst compound exists, a protective layer for protecting the coating layer is often formed. However, as described below, by forming the chemical conversion coating layer with an inorganic component, the chemical conversion coating layer can be configured without providing a protective layer. Here, the inorganic component refers to a component that does not contain an organic resin.

[0104] After impurities such as oil and surface oxides attached to the surface of the metal plate 10 are removed by a known degreasing process and a cleaning process, the inorganic coating layer 30 is formed by a chemical conversion treatment. The inorganic coating layer 30 is preferably composed of inorganic components such as silane compounds and zirconium oxide compounds containing at least one of Si and Zr. In addition, the inorganic coating layer 30 may also contain an inorganic component containing at least one of P and V.

[0105] The inorganic coating layer 30 contains inorganic components having the above-mentioned elements, thereby improving the film-forming properties after application of the chemical conversion treatment liquid, the barrier properties (density) of the coating to corrosion factors such as moisture and corrosive ions, and the adhesion of the coating to the surface of the metal plate, which helps to improve the corrosion resistance of the coating.

[0106] Among them, as the inorganic component containing Si, for example, γ-(2-aminoethyl)aminopropyltrimethoxysilane, γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropyltriethoxysilane, etc. can be listed. In addition, as the inorganic component containing Zr, for example, zirconium carbonate, ammonium zirconium carbonate, potassium zirconium carbonate, sodium zirconium carbonate, ammonium zirconium carbonate, etc. can be listed.

[0107] In addition, examples of inorganic components containing P include phosphoric acid, orthophosphoric acid, metaphosphoric acid, pyrophosphoric acid, triphosphoric acid, tetraphosphoric acid and other phosphoric acids and their salts, ammonium dihydrogen phosphate, etc. Examples of inorganic components containing V include ammonium metavanadate (V), potassium metavanadate (V), sodium metavanadate (V), vanadium sulfate (IV), etc.

[0108] In the inorganic coating layer 30 of the present embodiment, various inorganic components as described above can be used alone or in combination. In addition, the contents of various inorganic components as described above can also be adjusted appropriately.

[0109] The average thickness d2 of the inorganic coating layer 30 is preferably 0.05 μm or more, more preferably 0.10 μm or more. Thus, the inorganic coating layer 30 can be uniformly formed on the surface of the metal plate 10, and various effects produced by setting the above-mentioned chemical conversion coating layer can be stably presented. In addition, the average thickness d2 of the inorganic coating layer 30 is preferably 5.00 μm or less, more preferably 1.00 μm or less, further preferably less than 1.00 μm, further preferably 0.80 μm or less, 0.60 μm or less, or 0.50 μm or less. Thus, the inorganic coating layer 30 can be uniformly formed on the surface of the metal plate 10, and various effects produced by setting the above-mentioned chemical conversion coating layer can be stably presented.

[0110] In addition, similarly to the photocatalyst layer 20 , the inorganic coating layer 30 of the present embodiment preferably further contains at least one element selected from the group consisting of Zn, Cu, Fe, Ni, and Ag.

[0111] The total content of at least one element selected from the group consisting of Zn, Cu, Fe, Ni, and Ag in the inorganic coating layer 30 is preferably 0.2% by mass or more in terms of metal element conversion. By making the total content of the above-mentioned metal elements 0.2% by mass or more, the above-mentioned effect can be presented in a more preferred state. The total content of the above-mentioned metal elements is more preferably 0.6% by mass or more, and more preferably 1.0% by mass or more. On the other hand, the total content of at least one element selected from the group consisting of Zn, Cu, Fe, Ni, and Ag in the inorganic coating layer 30 is preferably 10.0% by mass or less in terms of metal element conversion. By making the total content of the above-mentioned metal elements 10.0% by mass or less, it is possible to ensure the content of the photocatalyst compound while making the above-mentioned effect present in an unsaturated manner. The total content of the above-mentioned metal elements is more preferably 7.5% by mass or less, and more preferably 5.0% by mass or less.

[0112] In addition, if Figure 2B As schematically shown above, the coated metal plate 1 of the present embodiment may further include various well-known layers between the photocatalyst layer 20 and the inorganic coating layer 30 .

[0113] Here, in Figure 2A and Figure 2B In such a case, the total thickness d from the surface of the metal plate 10 to the outermost surface of the photocatalyst layer 20 is T (=d1+d2+α) is also set to 15.00 μm or less. This can suppress the reduction in manufacturing simplicity and processability, and ensure the dissolution path of zinc from the zinc-containing metal layer 13 so that zinc can be fully dissolved, and the desired photocatalytic effect is uniformly exhibited throughout the photocatalyst layer 20. The total thickness d from the surface of the metal plate 10 to the outermost surface of the photocatalyst layer 20 is T (=d1+d2+α) is preferably 10.00 μm or less, more preferably 7.00 μm or less, further preferably 1.00 μm or less, less than 1.00 μm, 0.90 μm or less, 0.80 μm or less, or 0.70 μm or less.

[0114] <Modification 2>

[0115] The coated metal plate 1 of the present embodiment may include a resin coating layer 40 as an example of a third coating layer further below the inorganic coating layer 30 in addition to the inorganic coating layer 30 located between the metal plate 10 and the photocatalyst layer 20 .

[0116] Below, while referring to Figure 3A and Figure 3B , while explaining the resin coating layer 40 in detail. Figure 3A and Figure 3B This is an explanatory diagram schematically showing another example of the structure of the coated metal plate according to the present embodiment.

[0117] Figure 3A and Figure 3B Schematic diagram schematically showing the layer structure of the coated metal plate 1 in which a resin coating layer 40 as an example of the third coating layer is provided. In this case, the coated metal plate 1 of the present embodiment has the resin coating layer 40 as an example of the third coating layer below the inorganic coating layer 30 as described above.

[0118] The resin coating layer 40 is formed by chemical conversion treatment after impurities such as oil and surface oxides adhering to the surface of the metal plate 10 are removed in a known degreasing process and cleaning process.

[0119] The resin coating layer 40 of the present embodiment may contain, for example, a resin, or may further contain one or more selected from the group consisting of a silane coupling agent, a zirconium compound, silicon dioxide, phosphoric acid and its salt, a fluoride, a vanadium compound, and tannin or tannic acid. By containing these substances, the film-forming property after the chemical conversion treatment liquid is applied, the barrier property (density) of the coating to corrosion factors such as moisture and corrosive ions, and the adhesion of the coating to the surface of the metal plate are further improved, which helps to improve the corrosion resistance of the coating.

[0120] In particular, when the resin coating layer 40 contains at least one of a silane coupling agent and a zirconium compound, a cross-linked structure is formed in the resin coating layer 40 to strengthen the bond with the metal plate surface, thereby further improving the adhesion and barrier properties of the coating.

[0121] When the resin coating layer 40 contains one or more of silicon dioxide, phosphoric acid and its salts, fluorides, or vanadium compounds, it can further improve corrosion resistance by functioning as an inhibitor to form a precipitated film or a passivation film on the metal plate surface.

[0122] Hereinafter, details of each constituent component that can be contained in the above-mentioned resin coating layer 40 will be described with examples.

[0123] [Resin]

[0124] As the resin, for example, known organic resins such as polyester resin, polyurethane resin, epoxy resin, phenolic resin, acrylic resin, polyolefin resin, etc. can be used. In order to further improve the adhesion with the metal plate, it is preferred to use at least one of the resins (polyester resin, polyurethane resin, epoxy resin, acrylic resin, etc.) having a forced site and a polar functional group in the molecular chain. The resin can be used alone or in combination of two or more.

[0125] The content of the resin in the resin coating layer 40 is preferably 0% by mass or more, more preferably 1% by mass or more, relative to the solid content of the coating. Thus, the corrosion resistance can be improved. In addition, the content of the resin in the resin coating layer 40 is preferably 85% by mass or less, more preferably 60% by mass or less, and further preferably 40% by mass or less, relative to the solid content of the coating. By making the content of the resin 85% by mass or less, the corrosion resistance of the coating can be improved while ensuring the performance required as a coating other than corrosion resistance.

[0126] [Silane coupling agent]

[0127] Examples of the silane coupling agent include γ-(2-aminoethyl)aminopropyltrimethoxysilane, γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropyltriethoxysilane, γ-(2-aminoethyl)aminopropylmethyldiethoxysilane, γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropyltriethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, N-β-(N-vinylbenzylamino)silane ethyl)-γ-aminopropyltrimethoxysilane, N-β-(N-vinylbenzylaminoethyl)-γ-aminopropylmethyldimethoxysilane, N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltriethoxysilane, N-β-(N-vinylbenzylaminoethyl)-γ-aminopropylmethyldiethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropylmethyldimethoxysilane, γ-glycidyloxypropyltriethoxysilane, γ-glycidyloxypropylmethyldiethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-mercaptopropylmethyldimethoxysilane Oxysilane, γ-mercaptopropyl triethoxysilane, γ-mercaptopropyl methyldiethoxysilane, methyltrimethoxysilane, dimethyldimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, vinyltriacetoxysilane, γ-chloropropyltrimethoxysilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropyltriethoxysilane, γ-chloropropylmethyldiethoxysilane, hexamethyldisilazane, γ-anilinopropyltrimethoxysilane, γ-anilinopropylmethyldimethoxysilane, γ-anilinopropyltriethoxysilane, γ-anilinopropylmethyldiethoxysilane, vinyl Trimethoxysilane, vinylmethyldimethoxysilane, vinyltriethoxysilane, vinylmethyldiethoxysilane, octadecyldimethyl[3-(trimethoxysilyl)propyl]ammonium chloride, octadecyldimethyl[3-(methyldimethoxysilyl)propyl]ammonium chloride, octadecyldimethyl[3-(triethoxysilyl)propyl]ammonium chloride, octadecyldimethyl[3-(methyldiethoxysilyl)propyl]ammonium chloride, γ-chloropropylmethyldimethoxysilane, γ-mercaptopropylmethyldimethoxysilane, methyltrichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, etc. The amount of silane coupling agent added in the chemical conversion treatment agent for forming the resin coating layer 40 can be, for example, 2 to 80 g / L. By making the amount of silane coupling agent added 2 g / L or more, the adhesion to the metal plate surface can be improved, and the processing adhesion of the coating film can be improved. In addition, by setting the amount of the silane coupling agent added to 80 g / L or less, the cohesive force of the coating can be maintained and the processing adhesion of the coating can be improved. The silane coupling agents listed above may be used alone or in combination of two or more.

[0128] [Zirconium compounds]

[0129] As zirconium compounds, for example, zirconium n-propyl ester, zirconium n-butoxide, zirconium tetraacetylacetonate, zirconium monoacetylacetonate, zirconium diacetylacetonate, zirconium monoethyl acetoacetate, zirconium diethyl acetoacetate, zirconium acetate, zirconium monostearate, zirconium carbonate, ammonium zirconium carbonate, potassium zirconium carbonate, sodium zirconium carbonate, etc. can be cited. The amount of zirconium compound added in the chemical conversion treatment agent for forming the resin coating layer 40 can be, for example, 2 to 80 g / L. By making the amount of zirconium compound added 2 g / L or more, it is possible to improve the adhesion to the surface of the metal plate and improve the processing adhesion of the coating. In addition, by making the amount of zirconium compound added 80 g / L or less, it is possible to maintain the cohesive force of the coating and improve the processing adhesion of the coating. The zirconium compound can be used alone or in combination of two or more.

[0130] [Silicon dioxide]

[0131] As silica, for example, commercially available silica gels such as "SNOWTEX N", "SNOWTEX C", "SNOWTEX UP", "SNOWTEX PS" manufactured by Nissan Chemical Co., Ltd., "Adelite AT-20Q" manufactured by ADEKA Co., Ltd., or powdered silica such as AEROSIL#300 manufactured by Japan AEROSIL Co., Ltd. can be listed. The silica can be appropriately selected according to the desired performance of the coated metal plate. The amount of silica added in the chemical conversion treatment agent for forming the resin coating layer 40 is preferably 1 to 40 g / L. By making the amount of silica added be 1 g / L or more, the processing adhesion of the coating can be improved. In addition, by making the amount of silica added be 40 g / L or less, it is possible to seek the effect of taking into account both processing adhesion and corrosion resistance while suppressing the increase in cost.

[0132] [Phosphoric acid and its salts]

[0133] Phosphoric acid and its salts include, for example, phosphoric acids such as orthophosphoric acid, metaphosphoric acid, pyrophosphoric acid, triphosphoric acid, tetraphosphoric acid and their salts; ammonium salts such as triammonium phosphate and diammonium hydrogen phosphate; phosphonic acids such as aminotri(methylenephosphonic acid), 1-hydroxyethylidene-1,1-diphosphonic acid, ethylenediaminetetra(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid) and their salts; organic phosphoric acids such as phytic acid and their salts. In addition, salts of phosphoric acid other than ammonium salts include metal salts with Na, Mg, Al, K, Ca, Mn, Ni, Zn, Fe and the like. Phosphoric acid and its salts may be used alone or in combination of two or more.

[0134] In addition, the content of phosphoric acid and its salt is preferably more than 0 mass % relative to the film solid component, more preferably more than 1 mass %. In addition, the content of phosphoric acid and its salt is preferably less than 20 mass % relative to the film solid component, more preferably less than 10 mass %. By making the content of phosphoric acid and its salt become less than 20 mass %, it is possible to prevent the embrittlement of the film, and prevent the reduction of the processing adhesion of the film when the coated metal plate is formed.

[0135] [Fluoride]

[0136] Examples of the fluoride include ammonium zirconium fluoride, ammonium silicofluoride, ammonium titanate fluoride, sodium fluoride, potassium fluoride, calcium fluoride, lithium fluoride, titanic hydrofluoric acid, zirconic hydrofluoric acid, etc. These fluorides may be used alone or in combination of two or more.

[0137] In addition, the content of fluoride is preferably more than 0 mass % relative to the film solid component, more preferably more than 1 mass %. In addition, the content of fluoride is preferably less than 20 mass % relative to the film solid component, more preferably less than 10 mass %. By making the content of fluoride less than 20 mass %, it is possible to prevent the embrittlement of the film, and prevent the reduction of the processing adhesion of the film when the coated metal plate is subjected to forming processing.

[0138] [Vanadium compounds]

[0139] Examples of the vanadium compound include vanadium compounds having an oxidation number of 4 to 2, such as vanadium pentoxide, metavanadic acid, ammonium metavanadate, sodium metavanadate, and vanadium trichloride, which are obtained by reducing a pentavalent vanadium compound such as vanadium pentoxide, metavanadic acid, ammonium metavanadate, sodium metavanadate, and vanadium trichloride with a reducing agent to a divalent to tetravalent vanadium compound, vanadium trioxide, vanadium dioxide, vanadium oxysulfate, vanadium oxyoxalate, vanadium oxyacetylacetonate, vanadium acetylacetonate, vanadium trichloride, vanadium phosphomolybdic acid, vanadium sulfate, vanadium dichloride, and vanadium oxide, etc. The vanadium compound may be used alone or in combination of two or more.

[0140] In addition, the content of the vanadium compound is preferably 0% by mass or more relative to the film solid component, more preferably 1% by mass or more. In addition, the content of the vanadium compound is preferably 20% by mass or less relative to the film solid component, more preferably 10% by mass or less. By making the content of the vanadium compound be 20% by mass or less, the embrittlement of the film can be prevented, and the reduction of the processing adhesion of the film when the coated metal plate is formed can be prevented.

[0141] [Tannin or tannic acid]

[0142] Any of hydrolyzable tannins and condensed tannins can be used as tannin or tannic acid. Examples of tannin and tannic acid include witch hazel tannin, gallnut tannin, gallic tannin, myrobalan tannin, divi-divi tannin, algarovilla tannin, Valonia tannin, catechin, etc. The amount of tannin or tannic acid added in the chemical conversion treatment agent used to form the resin coating layer 40 can be 2 to 80 g / L. By making the amount of tannin or tannic acid added 2 g / L or more, the adhesion to the metal plate surface can be improved, and the processing adhesion of the coating can be improved. In addition, by making the amount of tannin or tannic acid added 80 g / L or less, the cohesion of the coating can be maintained, and the processing adhesion of the coating can be improved.

[0143] In addition, the resin coating layer 40 may contain a colorant in addition to the above-mentioned components. This allows the appearance of the coated metal plate 1 of the present embodiment to be set to a desired color tone, and the design of the coated metal plate 1 can be further improved.

[0144] Here, the type and content of the colorant contained in the resin coating layer 40 are not particularly specified and may be adjusted as appropriate.

[0145] In addition, an acid, a base, or the like may be added to the chemical conversion treatment agent for forming the resin coating layer 40 for adjusting the pH within a range that does not impair the performance.

[0146] The average thickness d3 of the resin coating layer 40 is preferably 0.20 μm or more, more preferably 0.50 μm or more, and further preferably 2.50 μm or more. Thus, the resin coating layer 40 can be uniformly formed on the surface of the metal plate 10, and various effects produced by providing the coating layer as described above can be stably presented. In addition, the average thickness d3 of the resin coating layer 40 is preferably 60.00 μm or less, more preferably 30.00 μm or less, and further preferably 15.00 μm or less, 1.00 μm or less, less than 1.00 μm, or 0.80 μm or less. Thus, the resin coating layer 40 can be uniformly formed on the surface of the metal plate 10, and various effects produced by providing the coating layer as described above can be stably presented.

[0147] In addition, if Figure 3B As schematically shown above, the coated metal plate 1 of the present embodiment may further include various well-known layers between the inorganic coating layer 30 and the resin coating layer 40 .

[0148] Here, in Figure 3A and Figure 3B In such a case, the total thickness d from the surface of the metal plate 10 to the outermost surface of the photocatalyst layer 20 isT (=d1+d3+d4+α) is set to 60.00 μm or less. This can suppress the reduction in manufacturing simplicity and processability, ensure the dissolution path of zinc from the zinc-containing metal layer 13, and allow zinc to dissolve sufficiently. Moreover, the desired photocatalytic effect is uniformly exhibited throughout the photocatalyst layer 20. The total thickness d from the surface of the metal plate 10 to the outermost surface of the photocatalyst layer 20 is T (=d1+d3+d4+α) is preferably 15.00 μm or less, more preferably 10.00 μm or less, further preferably 7.00 μm or less, further preferably 1.00 μm or less, less than 1.00 μm, 0.90 μm or less, 0.80 μm or less, or 0.70 μm or less.

[0149] Here, in each of the above-described modified examples, when the coated metal plate 1 was subjected to the antiviral test prescribed in JIS R1756:2020 for 4 hours, the concentration of zinc ions eluted into the virus-containing liquid was also within the range of 0.60 to 5.00 mass %.

[0150] In addition, Figure 2A to Figure 3A In the figure, the case where each layer is provided on one side of the metal plate 10 is shown, but each layer may be provided on both sides of the metal plate 10. In this case, the total thickness d from the surface of the metal plate 10 to the surface of the photocatalyst layer 20 is T The thickness of each surface of the coated metal plate 1 is 60.00 μm or less.

[0151] Above, while referring to Figure 1 to Figure 3B , while describing in detail the coated metal plate according to the first embodiment of the present invention.

[0152] <Method for measuring the average thickness of each layer>

[0153] Here, the average thickness of each layer including the photocatalyst layer can be measured by observing the layer of interest from the cross-sectional direction with a microscope. As a method for preparing a sample observed from the cross-sectional direction, for example, a method of grinding the observation surface by embedding in a resin, a method of performing FIB processing, a slicing method, and other known methods can be used. In addition, as for the type of microscope, a known device such as SEM, TEM, etc. can be used.

[0154] (Method for manufacturing coated metal sheet)

[0155] The coated metal plate of the present embodiment as described above can be manufactured by applying a photocatalyst treatment agent for forming a photocatalyst layer 20, an inorganic chemical conversion treatment agent for forming an inorganic coating layer 30, an organic chemical conversion treatment agent for forming a resin coating layer 40, etc. in a manner to form a desired layer structure, after which the coating is dried and sintered, based on various pre-treatments such as cleaning the surface of the metal plate 10 serving as the base material as needed.

[0156] Here, the coating of various coating materials can be generally performed by known coating methods such as roll coating, curtain coating, air spray coating, airless spray coating, dipping, bar coating, brush coating, etc. Roll coating is particularly preferred because it can stably coat thin films having the characteristics of the product.

[0157] The conditions for drying and calcining are not particularly limited and may be appropriately set according to the coating material used and the like.

[0158] <<Second Implementation Method>>

[0159] Next, a coated metal plate according to a second embodiment of the present invention will be described in detail.

[0160] A second embodiment of the present invention relates to a method in which a coated metal plate having a metal plate and a coating layer located on at least one surface of the metal plate has a first coating layer as a coating layer, wherein the first coating layer is located on the outermost surface of the coated metal plate and contains a compound having photocatalytic activity and 0.2 to 20.0 mass % of zinc element calculated as metallic Zn.

[0161] (For painted metal sheets)

[0162] <Structure of painted metal sheet>

[0163] Below, first, while referring to Figure 4 , while describing the structure of a coated metal plate according to a second embodiment of the present invention. Figure 4 This is an explanatory diagram schematically showing an example of the structure of the coated metal plate according to the present embodiment.

[0164] like Figure 4 As schematically shown, the coated metal plate 3 according to the second embodiment of the present invention has a coating layer on at least one surface of the metal plate, and includes at least a metal plate 10 and a photocatalyst layer 25 as an example of a first coating layer as the coating layer.

[0165] [For metal plate 10]

[0166] In the coated metal plate 3 of the present embodiment, the metal plate 10 uses various parent metals 11 as blanks to form the parent material of the metal plate 10. Here, various metal plates can be used as the parent metal 11. As such a metal plate, for example, various steel plates, aluminum plates, stainless steel plates, etc. can be listed, and it can be selected according to the strength and characteristics required by the parent metal 11.

[0167] In the coated metal plate 3 of the present embodiment, various plating layers may be provided on the surface of the base metal 11 constituting the metal plate 10. Here, as the various plating layers, plating layers not containing zinc may be provided.

[0168] Here, the thickness of the metal plate 10 as described above is not particularly limited, and may be appropriately set according to the mechanical strength (for example, tensile strength, etc.), workability, etc. required for the coated metal plate 3 of the present embodiment.

[0169] In addition, various patterns such as a wire drawing pattern and a zinc pattern may be present on the surface of the metal plate 10 along the rolling direction of the base metal 11. By providing such patterns, the design of the coated metal plate 3 can be further improved.

[0170] [For the photocatalyst layer 25]

[0171] In the coated metal plate 3 of this embodiment, as Figure 4 As schematically shown, the photocatalyst layer 25 as an example of the first coating layer is a layer located on the outermost surface of the coating layer in at least one surface of the metal plate 10. The photocatalyst layer 25 is a layer containing at least a compound having photocatalytic activity (hereinafter, sometimes abbreviated as "photocatalyst compound") and element Zn.

[0172] The photocatalyst layer 25 of the present embodiment contains a compound having photocatalytic activity, and the compound having the photocatalytic activity generates a photocatalytic reaction due to light (especially light in the ultraviolet to visible light band) incident on the photocatalyst layer 25. As a result, various photocatalytic effects, including antiviral effects and bactericidal effects, are exhibited in the photocatalyst layer 25 of the present embodiment. As a result, the coated metal plate 3 of the present embodiment can achieve various characteristics, including antiviral effects and bactericidal effects.

[0173] In addition, since the photocatalyst layer 25 of the present embodiment contains the element Zn, the element Zn contained in the photocatalyst layer 25 plays the same function as the function of the Zn contained in the zinc-containing metal layer 13 described in the first embodiment. As a result, the dissolution of zinc into the virus-containing liquid in the antiviral test specified in JIS R1756:2020 discovered by the present inventors occurs. As a result, the coated metal plate 3 of the present embodiment can play the same effect as the effect of the coated metal plate 1 of the first embodiment described above, and the antiviral function of the coated metal plate 3 can be further improved over a longer period of time using a simpler method.

[0174] In addition, the photocatalyst compound contained in the photocatalyst layer 25 of the present embodiment is the same photocatalyst compound as the photocatalyst compound contained in the photocatalyst layer 20 of the first embodiment, and has the same effect as the photocatalyst compound contained in the photocatalyst layer 20 of the first embodiment. Therefore, the detailed description of the photocatalyst compound is omitted below.

[0175] In the photocatalyst layer 25 of the present embodiment, the content of the element Zn contained in the photocatalyst layer 25 is 0.2% by mass or more in terms of metal Zn. When the content of Zn is less than 0.2% by mass, the amount of zinc dissolved from the photocatalyst layer 25 is too small, and as a result, the antibacterial effect described above cannot be exhibited. By making the content of Zn above 0.2% by mass, the antibacterial effect described above can be exhibited. The content of the above-mentioned element Zn is more preferably 0.6% by mass or more, and more preferably 1.0% by mass or more.

[0176] On the other hand, the content of Zn in the photocatalyst layer 25 is 20.0% by mass or less in terms of metal Zn. When the content of Zn is greater than 20.0% by mass, the amount of zinc dissolved from the photocatalyst layer 25 becomes too much and the compactness of the photocatalyst layer 25 is reduced, and corrosion factors easily enter from the outside. As a result, the corrosion resistance of the coated metal plate 3 is reduced. By making the total content of the above-mentioned element Zn less than 20.0% by mass, it is possible to ensure the content of the photocatalyst compound while making the above-mentioned effect appear in an unsaturated manner, and the corrosion resistance of the coated metal plate 3 can also be ensured. The total content of the above-mentioned element Zn is preferably less than 18.0% by mass, more preferably less than 16.0% by mass, further preferably less than 5.0% by mass, and further preferably less than 3.5% by mass, or less than 2.5% by mass.

[0177] In addition, the photocatalyst layer 25 preferably also contains at least one element of Si and Zr, and the total concentration of the element is 5% by mass or more when converted to silicon dioxide for Si and to zirconium oxide for Zr. In other words, the photocatalyst layer 25 is preferably an inorganic coating having a skeleton of an inorganic component having a three-dimensional network structure containing at least one element of Si and Zr and containing impurities according to circumstances, and the total concentration of at least one element of Si and Zr is 5% by mass or more when converted to silicon dioxide for Si and to zirconium oxide for Zr. By containing at least one element of Si and Zr at the above-mentioned concentration, a photocatalyst layer 25 with better corrosion resistance can be achieved. The total content of at least one element of Si and Zr is more preferably 10% by mass or more. Here, the inorganic component refers to a component that does not contain an organic resin.

[0178] In addition, it is preferred that the photocatalyst layer 25 also contains at least one element of Si and Zr, and the total concentration of the element is 50% by mass or less when converted to silicon dioxide for Si and zirconium oxide for Zr. By containing at least one element of Si and Zr at the above-mentioned concentration, a photocatalyst layer 25 with better corrosion resistance can be achieved. The total content of at least one element of Si and Zr is more preferably 40% by mass or less. Here, the contained Si or Zr is preferably excellent in light transmittance, and is preferably an inorganic component that is not easily affected by decomposition caused by a photocatalyst. As such inorganic components containing Si and Zr, for example, silicon dioxide and zirconium oxide can be listed.

[0179] In addition, the photocatalyst layer 25 preferably contains at least one element selected from the group consisting of Cu, Fe, Ni, and Ag in addition to the above-mentioned photocatalyst compound, Si, and Zr. Here, the elements Cu, Fe, Ni, and Ag are elements that promote the dissolution of zinc from the photocatalyst layer 25, and therefore, more zinc is dissolved from the photocatalyst layer 25 by the photocatalyst layer 25 also containing these elements, so it is preferred. Moreover, the elements Cu and Ag are also elements that exhibit antibacterial effects, and therefore, they are particularly preferred.

[0180] The total content of at least one element selected from the group consisting of Cu, Fe, Ni, and Ag in the photocatalyst layer 25 is preferably 0.2% by mass or more in terms of metal element conversion. By making the total content of the above-mentioned metal elements to be 0.2% by mass or more, the above-mentioned effect can be presented in a more preferred state. The total content of the above-mentioned metal elements is more preferably 0.6% by mass or more, and further preferably 1.0% by mass or more. On the other hand, the total content of at least one element selected from the group consisting of Cu, Fe, Ni, and Ag in the photocatalyst layer 25 is preferably 5.0% by mass or less in terms of metal element conversion. By making the total content of the above-mentioned metal elements to be 5.0% by mass or less, the above-mentioned effect can be presented in an unsaturated manner while ensuring the content of the photocatalyst compound. The total content of the above-mentioned metal elements is more preferably 3.5% by mass or less, and further preferably 2.5% by mass or less.

[0181] Furthermore, the photocatalyst layer 25 containing the above-mentioned photocatalyst compound may contain an adsorbent such as an antimicrobial agent, activated carbon, or zeolite as necessary within a range that does not impair the effects of the present invention.

[0182] The average thickness d1′ of the photocatalyst layer 25 (in Figure 4 In the case of the layer structure shown in FIG. 1 , the total thickness d from the surface of the metal plate 10 to the outermost surface of the photocatalyst layer 25 (which can also be regarded as the outermost surface of the coating layer) is T . ) is 0.05 μm or more. When the average thickness d1' of the photocatalyst layer 25 is less than 0.05 μm, it is difficult to form the above-mentioned photocatalyst layer 25 uniformly, resulting in uneven photocatalytic effect, and therefore, it is not preferred. By setting the average thickness d1' to be greater than 0.05 μm, the dissolution path of zinc from the photocatalyst layer 25 can be ensured so that zinc is fully dissolved, and the desired photocatalytic effect is uniformly presented throughout the photocatalyst layer 25.

[0183] On the other hand, the average thickness d1' (in Figure 4 In the case of the layer structure shown in FIG. 1 , the total thickness d from the surface of the metal plate 10 to the outermost surface of the photocatalyst layer 25 is T. ) is 5.00μm or less. In the case where the average thickness d1' of the photocatalyst layer 25 is greater than 5.00μm, the obtained photocatalytic effect is saturated, and on the other hand, the manufacturing cost increases, so it is not preferred. In addition, it is difficult to fully ensure the amount of zinc dissolved from the photocatalyst layer 25, so from this point of view, it is not preferred. In addition, the photocatalyst layer is an inorganic coating, so the processability is reduced. By setting the average thickness d1' to less than 5.00μm, the reduction in manufacturing simplicity and processability is suppressed, and the dissolution path of zinc from the photocatalyst layer 25 is ensured so that zinc is fully dissolved, and the desired photocatalytic effect can be uniformly presented throughout the photocatalyst layer 25.

[0184] Usually, light passes through the photocatalyst layer 25 without hitting the photocatalyst compound with a certain degree of probability. In the past, such light that does not react with the photocatalyst compound has been unable to obtain a photocatalytic effect. In this embodiment, by reflecting such light on the surface of the metal plate 10, the probability of light incident on the photocatalyst layer 25 colliding with the photocatalyst compound can be increased. Therefore, in this embodiment, the photocatalytic effect can be further improved. Figure 4 In the case of the layer structure shown in FIG. 1 , the total thickness d from the surface of the metal plate 10 to the outermost surface of the photocatalyst layer 25 is T Of course, it becomes below 5.00μm. As a result, the incident light reflected from the surface of the metal plate 10 (in other words, the interface between the metal plate 10 and the photocatalyst layer 25) can be used for the photocatalytic reaction caused by the photocatalyst compound. Therefore, the cost can be suppressed and the photocatalytic effect can be further improved.

[0185] The average thickness d1' of the photocatalyst layer 25 is preferably 0.10 μm or more, more preferably 0.15 μm or more. In addition, the average thickness d1' of the photocatalyst layer 20 is preferably 2.00 μm or less, more preferably 1.00 μm or less, further preferably less than 1.00 μm, and even more preferably 0.80 μm or less, 0.60 μm or less, or 0.50 μm or less.

[0186] In addition, Figure 4 In FIG. 1 , an embodiment in which the photocatalyst layer 25 is formed on one surface of the metal plate 10 is illustrated, but the photocatalyst layer 25 may be formed on both surfaces of the metal plate 10 .

[0187] <Concentration of zinc ions eluted into virus-containing fluid in antiviral test>

[0188] The structure of the coated metal plate 3 described above is one of the conditions for making the concentration of zinc ions eluted into the virus-containing liquid within the range of 0.60 to 5.00 mass % when the antiviral test specified in JIS R1756:2020 is performed for 4 hours.

[0189] The reason why the above-mentioned structure is one of the conditions is that in the coated metal plate 3 of the present embodiment, the photocatalyst layer 25 is provided in an appropriate state, and the total thickness d from the surface of the metal plate 10 to the outermost surface of the photocatalyst layer 25 is 2.37mm / s. T Since the contents of Zn in the photocatalyst layer 25 are respectively within specific ranges, an appropriate amount of zinc can be eluted from the photocatalyst layer 25 .

[0190] In addition, by adjusting the Zn content in the photocatalyst layer 25, the total thickness d T , the amount of zinc eluted from the photocatalyst layer 25 can be controlled to a desired state.

[0191] Here, when the zinc ion concentration in the virus-containing liquid is less than 0.60 mass %, it means that the amount of zinc eluted from the photocatalyst layer 25 is insufficient, and the antiviral function exhibited by the coated metal plate 3 cannot be further improved. The zinc ion concentration in the virus-containing liquid is preferably 0.90 mass % or more, and more preferably 1.20 mass % or more.

[0192] On the other hand, when the zinc ion concentration in the virus-containing liquid exceeds 5.00 mass %, the amount of zinc eluted from the photocatalyst layer 25 becomes too large, and the corrosion resistance of the metal plate 10 cannot be ensured. The zinc ion concentration in the virus-containing liquid is preferably 4.50 mass % or less, and more preferably 3.50 mass % or less.

[0193] In addition, in the coated metal plate 3 of the present embodiment, the total content of the element (more specifically, ion) present in the coating layer and having a potential higher than zinc is preferably less than 20.0 mass % in terms of metal element conversion. Here, as an element with a potential higher than zinc, for example, Cu, Ag, etc. can be cited. By setting the total content of the element in the coating layer and having a potential higher than zinc to less than 20.0 mass %, the zinc ion concentration in the above-mentioned virus-containing liquid can be set to less than 5.00 mass %, and it is possible to seek to further take into account excellent antiviral properties and excellent corrosion resistance. The total content of the element in the coating layer and having a potential higher than zinc is more preferably less than 15.0 mass %, more preferably less than 11.0 mass %, and more preferably less than 7.5 mass %. In addition, the lower limit of the total content of the element in the coating layer and having a potential higher than zinc is not particularly specified, and can also be 0 mass %.

[0194] Here, the above antiviral test is carried out for 4 hours according to the method specified in JIS R1756: 2020. In addition, the concentration of zinc ions eluted into the virus-containing liquid may be measured by inductively coupled plasma (ICP) emission spectrometry.

[0195] <Variation Example-3>

[0196] have Figure 4 The coated metal plate 3 of the present embodiment having such a layer structure may also have more coating layers functioning as chemical conversion coating layers between the metal plate 10 and the photocatalyst layer 25. By providing the chemical conversion coating layer between the metal plate 10 and the photocatalyst layer 25, the adhesion between the metal plate 10 and the photocatalyst layer 25 can be further improved. Moreover, the corrosion resistance of the coated metal plate 3 of the present embodiment can be further improved.

[0197] Below, while referring to Figure 5A and Figure 5B , while explaining in detail more coating layers that function as a chemical conversion treatment coating layer. Figure 5A and Figure 5B This is an explanatory diagram schematically showing another example of the structure of the coated metal plate according to the present embodiment.

[0198] Figure 5A and Figure 5B The schematic diagram schematically shows the layer structure of the coated metal plate 3 in which an inorganic coating layer 30 that functions as a chemical conversion coating layer is provided as an example of a second coating layer. In this case, the coated metal plate 3 of the present embodiment has an inorganic coating layer 30 that is an example of a second coating layer between the metal plate 10 and the photocatalyst layer 25 as described above.

[0199] In addition, if Figure 5B As schematically shown above, the coated metal plate 3 of the present embodiment may further include various well-known layers between the photocatalyst layer 25 and the inorganic coating layer 30 .

[0200] Here, the inorganic coating layer 30 of the coated metal plate 3 of this embodiment has the same structure as the inorganic coating layer 30 of the coated metal plate 1 of the first embodiment of the present invention and has the same effects, so detailed description is omitted below.

[0201] The average thickness d2 of the inorganic coating layer 30 is preferably 0.05 μm or more, more preferably 0.10 μm or more. Thus, the inorganic coating layer 30 can be uniformly formed on the surface of the metal plate 10, and various effects produced by setting the above-mentioned chemical conversion coating layer can be stably presented. In addition, the average thickness d2 of the inorganic coating layer 30 is preferably 5.00 μm or less, more preferably 1.00 μm or less, further preferably less than 1.00 μm, and further preferably 0.80 μm or less, 0.60 μm or less, or 0.50 μm or less. Thus, the inorganic coating layer 30 can be uniformly formed on the surface of the metal plate 10, and various effects produced by setting the above-mentioned chemical conversion coating layer can be stably presented.

[0202] In addition, Figure 5A and Figure 5B In such a case, the total thickness d from the surface of the metal plate 10 to the outermost surface of the photocatalyst layer 25 is T (=d1'+d2+α) is also set to 60.00 μm or less. This can suppress the reduction in manufacturing simplicity and processability, and ensure the dissolution path of zinc from the photocatalyst layer 25 so that zinc can be fully dissolved, and further the desired photocatalytic effect can be uniformly presented throughout the photocatalyst layer 25. The total thickness d from the surface of the metal plate 10 to the outermost surface of the photocatalyst layer 25 is T (=d1′+d2+α) is preferably 15.00 μm or less, more preferably 10.00 μm or less, further preferably 7.00 μm or less, further preferably 1.00 μm or less, less than 1.00 μm, 0.90 μm or less, 0.80 μm or less, or 0.70 μm or less.

[0203] <Variation Example-4>

[0204] The coated metal plate 3 of the present embodiment may include, in addition to the inorganic coating layer 30 located between the metal plate 10 and the photocatalyst layer 25 , a resin coating layer 40 as an example of a third coating layer further below the inorganic coating layer 30 .

[0205] Below, while referring to Fig. 6A and Figure 6B , while explaining the resin coating layer 40 in detail. Fig. 6A and Figure 6B This is an explanatory diagram schematically showing another example of the structure of the coated metal plate according to the present embodiment.

[0206] Fig. 6A and Figure 6BSchematic diagram schematically showing the layer structure of the coated metal plate 3 in which a resin coating layer 40 as an example of the third coating layer is provided. In this case, the coated metal plate 3 of the present embodiment has a resin coating layer 40 as an example of the third coating layer below the inorganic coating layer 30 as described above.

[0207] In addition, if Figure 6B As schematically shown above, the coated metal plate 3 of the present embodiment may further include various well-known layers between the inorganic coating layer 30 and the resin coating layer 40 .

[0208] Here, the resin coating layer 40 of the coated metal plate 3 of this embodiment has the same structure as the resin coating layer 40 of the coated metal plate 1 of the first embodiment of the present invention and has the same effects, so detailed description is omitted below.

[0209] The average thickness d3 of the resin coating layer 40 is preferably 0.20 μm or more, more preferably 0.50 μm or more, and further preferably 2.50 μm or more. Thus, the resin coating layer 40 can be uniformly formed on the surface of the metal plate 10, and various effects produced by providing such a coating layer can be stably presented. In addition, the average thickness d3 of the resin coating layer 40 is preferably 60.00 μm or less, more preferably 30.00 μm or less, further preferably 12.00 μm or less, and further preferably 1.00 μm or less, less than 1.00 μm, or 0.90 μm or less. Thus, the resin coating layer 40 can be uniformly formed on the surface of the metal plate 10, and various effects produced by providing such a coating layer can be stably presented.

[0210] Here, in Fig. 6A and Figure 6B In such a case, the total thickness d from the surface of the metal plate 10 to the outermost surface of the photocatalyst layer 25 is T (=d1'+d3+d4+α) is also set to 60.00 μm or less. This can suppress the reduction in manufacturing simplicity and processability, and ensure the dissolution path of zinc from the photocatalyst layer 25 so that zinc can be fully dissolved, and further the desired photocatalytic effect can be uniformly presented throughout the photocatalyst layer 25. The total thickness d from the surface of the metal plate 10 to the outermost surface of the photocatalyst layer 25 is T (=d1′+d3+d4+α) is preferably 15.00 μm or less, more preferably 10.00 μm or less, further preferably 7.00 μm or less, further preferably 1.00 μm or less, less than 1.00 μm, 0.90 μm or less, 0.80 μm or less, or 0.60 μm or less.

[0211] Here, in each of the above-described modified examples, when the coated metal plate 3 was subjected to the antiviral test prescribed in JIS R1756:2020 for 4 hours, the concentration of zinc ions eluted into the virus-containing liquid was also within the range of 0.60 to 5.00 mass %.

[0212] In addition, Figure 5A to Figure 6B In the figure, the case where each layer is provided on one side of the metal plate 10 is shown, but each layer may be provided on both sides of the metal plate 10. In this case, the total thickness d from the surface of the metal plate 10 to the surface of the photocatalyst layer 25 is T The thickness of each surface of the coated metal plate 3 is 60.00 μm or less.

[0213] Above, while referring to Figures 4 to 6B , while describing in detail the coated metal plate according to the second embodiment of the present invention.

[0214] <Method for measuring the average thickness of each layer>

[0215] Here, the average thickness of each layer including the photocatalyst layer can be measured by observing the layer of interest from the cross-sectional direction using a microscope. As a method for preparing a sample observed from the cross-sectional direction, for example, a method of embedding in a resin, a method of grinding the observation surface, a method of FIB processing, a slicing method, etc. can be used. In addition, as the type of microscope, a known device such as SEM, TEM, etc. can be used.

[0216] (Method for manufacturing coated metal sheet)

[0217] After various pretreatments such as cleaning are performed on the surface of the metal plate 10 serving as the base material as needed, a photocatalyst treatment agent for forming a photocatalyst layer 25, an inorganic chemical conversion treatment agent for forming an inorganic coating layer 30, an organic chemical conversion treatment agent for forming a resin coating layer 40, etc. are applied in a manner to form a desired layer structure, and then the surface is dried and sintered, thereby manufacturing the coated metal plate of the present embodiment as described above.

[0218] Here, the coating of various coating materials can be generally carried out by known coating methods such as roll coating, curtain coating, air spray, airless spray, dipping, rod coating, brush coating, etc. Roll coating is particularly preferred because it can stably coat thin films having the characteristics of the product.

[0219] The conditions for drying and calcining are not particularly limited and can be appropriately set according to the coating material used and the like.

[0220] Example

[0221] Hereinafter, the coated metal sheet of the present invention will be specifically described while showing examples and comparative examples. In addition, the following examples are only examples of the coated metal sheet of the present invention, and the coated metal sheet of the present invention is not limited to the following examples.

[0222] As the metal plates to be the base materials of the coated metal plates, 9 types of metal plates were prepared as shown in Table 1 below. In Table 1, the 6 types of metal plates indicated as SD, ZL, GI, GL, AL, and GA are various plated steel plates with steel plates as the base materials. The plate thickness of each metal plate and the coating composition and adhesion amount / standard of each plated steel plate are shown in Table 1 below. In addition, for the stainless steel plate, a 20 g / m 2 The zinc-containing coating layer using zinc was formed with an adhesion amount of as stainless steel-2.

[0223] [Table 1]

[0224] Table 1

[0225]

[0226] As compounds having photocatalytic activity (photocatalyst compounds), 7 compounds shown in the following Table 2 were prepared. All the photocatalyst compounds were commercially available. Table 2 also lists the supported metal and the average particle size.

[0227] [Table 2]

[0228] Table 2

[0229]

[0230] <Organic chemical conversion treatment agent>

[0231] The raw materials of the water-based paint (chemical conversion treatment agent) used to form the organic chemical conversion treatment film used for the resin coating layer and the concentration in the dry film are shown in the following Table 3. The addition amount is adjusted so that the concentration of each component in the dry film becomes a predetermined concentration. Ion exchange water is added to adjust so that the solid content concentration of the treatment agent becomes 20% by mass. Each treatment agent is applied so as to become the dry film thickness shown in the following Tables 4-1, 4-2, and 6. Then, the metal plate is dried in an induction heating furnace so that the temperature reaches 150°C, and then water-cooled by spraying.

[0232] [Table 3]

[0233] Table 3

[0234]

[0235] <Photocatalyst treatment agent, inorganic chemical conversion treatment agent>

[0236] The preparation methods of the photocatalytic treatment agent and the inorganic chemical conversion treatment agent used are described below.

[0237] Considering storage stability, the inorganic chemical conversion treatment agent used to form the inorganic coating layer was adjusted so that the solid content concentration was 8% by mass. The concentration was adjusted by diluting with n-butanol. In addition, for some examples, the following inorganic chemical conversion treatment agent contained ammonium dihydrogen phosphate as a P source and sodium metavanadate as a V source. A photocatalyst treatment agent was prepared by adding a predetermined amount of the compound shown in Table 2 to the following inorganic chemical conversion treatment agent. The solid content concentration of the photocatalyst compound is shown in the following Table 4-1, Table 4-2, and Table 6.

[0238] (1) Inorganic chemical conversion treatment agent (Si system): Tetraethoxysilane (22.5 parts by mass), methacryloxypropyltrimethoxysilane (2.8 parts by mass) and n-butanol (26 parts by mass) were mixed and stirred at 60°C for 2 hours. While the mixture was stirred, a mixed solution of 26% by mass hydrochloric acid (3 parts by mass) and n-butanol (26 parts by mass) was added dropwise at 1 drop / second. Thereafter, the mixture was kept at 60°C for 2 hours while being stirred to obtain a treatment agent. A series of operations were carried out in a nitrogen atmosphere.

[0239] (2) Inorganic chemical conversion treatment agent (Zr system): n-butoxy zirconium (34.5 parts by mass), n-butanol (11.6 parts by mass), 1,5-diaminopentane (0.5 parts by mass) and yttrium nitrate (2.8 parts by mass) were mixed and stirred for 1 hour. Then, glacial acetic acid (4.8 parts by mass) was added and stirred for 40 hours. Then, concentrated nitric acid (0.6 parts by mass) was added dropwise at 1 drop / second and stirred for 2 hours to obtain a treatment agent. A series of operations were carried out in a nitrogen atmosphere.

[0240] In addition, in some examples, the above-mentioned photocatalyst treatment agent and inorganic chemical conversion treatment agent contain ultrafine particle zinc oxide (trade name: FZO) manufactured by Ishihara Sangyo Co., Ltd. as a Zn source, nanoparticle cuprous oxide (trade name: FRC-N10) manufactured by Furukawa Chemicals Co., Ltd. as a Cu source, Fe2O3 nanopowder (trade name: 544884) manufactured by Sigma-Aldrich Co., Ltd. as a Fe source, nickel nanopowder 50nm target product manufactured by Iwatani Sangyo Co., Ltd. as a Ni source, and Ag nanopowder (trade name: 576832) manufactured by Sigma-Aldrich Co., Ltd. as an Ag source.

[0241] Using the metal plates and photocatalyst compounds shown above, two coated metal plates each having the structures shown in Table 4-1, Table 4-2, and Table 6 below were manufactured by roller coating for each level. In addition, each layer was formed on a single surface of the metal plate. In addition, for some of the coated metal plates, the surface of the metal plate was subjected to design processing to form a brushed pattern. In addition, for some of the coated metal plates, a molten zinc plating bath containing 0.1% by mass of Sb and 0.2% by mass of Al was used, and the solidification rate of the molten zinc plating was adjusted, and a plated steel plate with a zinc flower pattern was used as a substrate.

[0242] The average film thickness of each layer in the above-mentioned coated metal plate is measured by embedding the obtained coated metal plate in a resin and observing the observation surface obtained by polishing the cross section with a microscope.

[0243] Furthermore, one of the obtained coated metal plates was subjected to an antiviral test specified in JIS R1756:2020 for 4 hours, and then the concentration of zinc ions eluted into the virus-containing liquid was measured according to the method described above.

[0244] A test piece was prepared using another coated metal plate obtained, and the test piece was evaluated from the viewpoints of antiviral property, working adhesion, and corrosion resistance. The detailed evaluation method is as follows.

[0245] <Antiviral properties>

[0246] The antiviral property was verified by measuring the virus infection titer in the following antiviral test according to the antiviral standard specified by the Photocatalyst Industry Association. More specifically, a test piece (size: 50x50mm) prepared from each coated metal plate was 2 ) is placed on a culture dish with the evaluation surface facing up, and a virus suspension containing bacteriophage Qβ is dripped onto the evaluation surface. Afterwards, a film is placed on the test piece to make the virus suspension close to the entire evaluation surface, and then the lid of the culture dish is closed. In a room simulating a regular office, the culture dish is left to stand for 4 hours in a room at 25°C with an illumination of 500 lux. Afterwards, the viruses on the surface of the film and the evaluation surface are cleaned, and the virus infection titer (unit: PFU, PFU: Plaque Forming Units) in the obtained cleaning solution is measured by plaque assay, and the concentration of dissolved zinc ions in the cleaning solution is measured using an inductively coupled plasma (ICP) emission spectrometer (7700X manufactured by Agilent).

[0247] Independently from the coated metal plates, the antiviral test was also conducted on each metal plate without a photocatalyst layer, and the virus infection titer of the metal plate without a photocatalyst layer was compared with that of the metal plate without a photocatalyst layer. The degree of reduction in the virus infection titer of the coated metal plate was evaluated as the activity value. 2 Above (in other words, if the activity value is 1×10 2 above), the use of the certification label specified by the Photocatalyst Industry Association is permitted. In view of this, the obtained activity value 1×10 2 The above results were judged as acceptable. Table 5-1, Table 5-2, and Table 7 below show the activity values ​​obtained by logarithmic expression.

[0248] <Processing Adhesion>

[0249] The test piece was subjected to 0T bending (180° bending) processing, and after peeling off the coating on the outside of the bending portion with an adhesive tape (transparent tape (registered trademark) manufactured by Nichiban Co., Ltd. with a width of 15 mm), the coating was observed to be attached to the tape side. In addition, the processing adhesion was evaluated according to the following evaluation criteria. In this adhesion test, the qualified level was set to 3 or more. Specifically, when the score was 4 or more, it was judged that the adhesion was excellent, and 3 or more was judged to be allowable (qualified level).

[0250] (Evaluation Criteria)

[0251] 5: No film attached to the tape side

[0252] 4: When the film peels off at several locations on the tape side, the peeling length on the steel plate side is less than 5% of the total length of the processed portion on one side of the test piece.

[0253] 3: When the film peels off at several locations on the tape side, the peeling length on the steel plate side is 5% or more and less than 10% of the total length of the processed portion on one side of the test piece.

[0254] 2: The film peels off on the tape side, and the peeling length on the steel plate side is 10% or more and less than 20% of the total length of the processed portion on one side of the test piece.

[0255] 1: The film peels off on the tape side, and the peeling length on the steel plate side is 20% or more of the total length of the processed portion on one side of the test piece

[0256] <Corrosion resistance of flat plate>

[0257] The end faces of the test pieces were sealed with tape and subjected to a 72-hour salt spray test (SST) in accordance with JIS Z 2371: 2015. After the test, the rust condition of the flat plate was observed and the corrosion resistance was evaluated according to the following evaluation criteria. The pass level was set to 3 or above.

[0258] (Evaluation Criteria)

[0259] 5: The white rust formation area is less than 1% of the total area of ​​one side of the test piece

[0260] 4: The white rust formation area is 1% or more and less than 5% of the total area of ​​one side of the test piece

[0261] 3: The white rust formation area is 5% or more and less than 10% of the total area of ​​one side of the test piece

[0262] 2: The white rust formation area is 10% or more and less than 30% of the total area of ​​one side of the test piece

[0263] 1: The white rust formation area is 30% or more relative to the total area of ​​one side of the test piece

[0264] <Corrosion resistance of processed parts>

[0265] For each test piece, a sample was obtained by processing (7 mm extrusion) according to the Erichsen test (JIS Z 2247: 2006). For this sample, the end surface was sealed with tape and a salt spray test (SST) according to JIS Z 2371 was performed for 72 hours. In addition, the rust condition of the processed part was observed after the test, and the corrosion resistance was evaluated according to the following evaluation criteria. The pass level was set to 3 or above.

[0266] (Evaluation Criteria)

[0267] 5: The white rust generation area is less than 5% of the total area of ​​the processed part of the test piece

[0268] 4: The white rust generation area is 5% or more and less than 10% of the total area of ​​the processed part of the test piece

[0269] 3: The white rust generation area is 10% or more and less than 30% of the total area of ​​the processed part of the test piece

[0270] 2: The white rust generation area is 30% or more and less than 50% of the total area of ​​the processed part of the test piece

[0271] 1: The white rust generation area is 50% or more of the total area of ​​the processed part of the test piece

[0272] The obtained results are summarized in the following Tables 5-1, 5-2 and 7.

[0273] It can be clearly seen from the following Tables 5-1, 5-2 and 7 that the coated metal plates according to the embodiments of the present invention exhibit excellent antiviral properties, processing adhesion and corrosion resistance. On the other hand, the evaluation results of the antiviral properties or processing adhesion of the coated metal plates according to the comparative examples of the present invention are unqualified.

[0274] [Table 4-1]

[0275]

[0276] [Table 4-2]

[0277]

[0278] [Table 5-1]

[0279] Table 5-1

[0280]

[0281] [Table 5-2]

[0282] Table 5-2

[0283]

[0284] [Table 6]

[0285]

[0286] [Table 7]

[0287] Table 7

[0288]

[0289] The preferred embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to this example. It is obvious that anyone with common knowledge in the technical field to which the present invention belongs can think of various variations or modifications within the scope of the technical ideas described in the claims, and these are also understood to belong to the protection scope of the present invention.

[0290] The embodiments disclosed this time are illustrative in all points and are not restrictive. The above-mentioned embodiments may also be omitted, replaced, and changed in various ways without departing from the structure and the main purpose of the scope of protection of the present invention as described in the attached claims and the following. For example, the constituent elements of the above-mentioned embodiments can be arbitrarily combined within the scope that does not impair their effects. In addition, of course, the functions and effects of each constituent element of the combination can be obtained from this arbitrary combination, and other functions and other effects that are obvious to those skilled in the art based on the description of this specification can be obtained.

[0291] In addition, the effects described in this specification are in principle for explanation or illustration and are not limiting. That is, the technology of the present invention can have other effects that are obvious to those skilled in the art based on the description of this specification together with or instead of the above effects.

[0292] Description of Reference Numerals

[0293] 1, 3, coated metal plate; 10, metal plate; 11, base metal; 13, zinc-containing metal layer; 20, 25, photocatalyst layer (first coating layer); 30, inorganic coating layer (second coating layer); 40, resin coating layer (third coating layer).

Claims

1. A coated metal plate comprising a metal plate and a coating layer located on at least one surface of the metal plate, The metal plate is a metal plate having a zinc-containing metal layer containing at least zinc on at least one surface. The coated metal plate has a first coating layer as the coating layer, the first coating layer is located on the outermost surface of the coated metal plate and contains at least a compound having photocatalytic activity. The average thickness of the first coating layer is 0.05 to 5.00 μm. The total thickness from the surface of the zinc-containing metal layer to the outermost surface of the first coating layer is 15.00 μm or less. When the antiviral test specified in JIS R1756:2020 was performed for 4 hours, the concentration of zinc ions eluted into the virus-containing liquid was 0.60 to 5.00% by mass.

2. The coated metal sheet according to claim 1, wherein: The thickness of the first coating layer is 0.05 to 0.95 μm. The total thickness from the surface of the zinc-containing metal layer to the outermost surface of the first coating layer is less than 1.0 μm.

3. The coated metal plate according to claim 1 or 2, wherein: The total content of elements having a higher potential than zinc in the coating layer is 0 to 20.0% by mass.

4. The coated metal sheet according to claim 1, wherein The first coating layer further contains at least one element selected from the group consisting of Zn, Cu, Fe, Ni, and Ag.

5. The coated metal sheet according to claim 1, wherein The first coating layer further contains at least one element of Si and Zr. The total content of the above elements is 5 to 50% by mass in terms of silicon dioxide for Si and in terms of zirconium oxide for Zr.

6. A coated metal plate comprising a metal plate and a coating layer located on at least one surface of the metal plate, The coated metal plate has a first coating layer as the coating layer, the first coating layer is located on the outermost surface of the coated metal plate, and contains a compound having photocatalytic activity and 0.2 to 20.0 mass % of zinc element in terms of metal Zn. The average thickness of the first coating layer is 0.05 to 5.00 μm. The total thickness from the surface of the metal plate to the outermost surface of the first coating layer is 60.0 μm or less. When the antiviral test specified in JIS R1756:2020 was performed for 4 hours, the concentration of zinc ions eluted into the virus-containing liquid was 0.60 to 5.00% by mass.

7. The coated metal plate according to claim 6, wherein: The total content of elements having a higher potential than zinc in the coating layer is 0 to 20.0% by mass.

8. The coated metal sheet according to claim 6 or 7, wherein: The first coating layer further contains at least one element selected from the group consisting of Cu, Fe, Ni, and Ag.

9. The coated metal plate according to claim 6, wherein: The first coating layer further contains at least one element of Si and Zr. The total content of the above elements is 5 to 50% by mass in terms of silicon dioxide for Si and in terms of zirconium oxide for Zr.

10. The coated metal sheet according to claim 1 or 6, wherein: The coated metal plate further comprises a second coating layer as the coating layer, the second coating layer being located below the first coating layer and being composed of an inorganic component. The second coating layer contains at least one element of Si and Zr as the inorganic component, The average thickness of the second coating layer is 0.05 to 5.00 μm.

11. The coated metal sheet according to claim 10, wherein: The second coating layer further contains at least one element of P and V as the inorganic component.

12. The coated metal sheet according to claim 10, wherein The second coating layer further contains at least one element selected from the group consisting of Zn, Cu, Fe, Ni, and Ag.

13. The coated metal sheet according to claim 10, wherein: The coated metal plate further comprises a third coating layer as the coating layer, the third coating layer being located below the second coating layer and containing a resin component. The average thickness of the third coating layer is 0.50 to 14.00 μm.

14. The coated metal sheet according to claim 13, wherein: The third coating layer further contains a colorant.

15. The coated metal plate according to claim 1 or 6, wherein The compound having photocatalytic activity is anatase-type titanium oxide.

16. The coated metal sheet according to claim 15, wherein The compound having photocatalytic activity is a metal-supported titanium oxide in which titanium oxide is supported by at least one metal of Cu and Fe.

17. The coated metal sheet according to claim 1, wherein The metal sheet is a zinc-based plated steel sheet having a zinc-based plating layer as the zinc-containing metal layer.

18. The coated metal sheet according to claim 17, wherein: The zinc-based plating layer is a plating layer containing 30 mass % or more of Zn in terms of metallic Zn.

19. The coated metal sheet according to claim 17, wherein: The zinc-based plating layer is any one of a zinc plating layer, a zinc-aluminum alloy plating layer, a zinc-aluminum-magnesium alloy plating layer, a zinc-nickel alloy plating layer, and a zinc-iron alloy plating layer.

20. The coated metal sheet according to claim 1 or 6, wherein: There are wires on the surface of the metal plate along the rolling direction of the metal plate.

21. The coated metal sheet according to claim 1, wherein There are zinc flower patterns on the surface of the zinc-containing metal layer.

Citation Information

Patent Citations

  • Precoated steel sheet

    JP2009131960A

  • Precoated metal plate having excellent resistance to contamination, manufacturing method therefor, and surface-treatment liquid

    CN102325649A

  • Zinc-coated steel sheet

    CN102378828A

  • Plated steel product, plated steel sheet and precoated steel sheet having excellent resistance to corrosion

    CN1342211A

  • Coated steel sheet with outstanding corrosion resistance and anti-contamination properties

    JP2002254556A